An Analysis of Grammatical Errors in Advertising Slogan - Agustina Sihombing; Mutiah Mutiah; Nurma Dhona Handayani (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
Language is a very important communication tool to be able to interact with each other. The language used in all activities, study, work, including the marketing of a product. Companies must have the capacity to create or control audiences (readers, or listeners) to buy the goods they offer. To tell more about a product, service or idea, companies use English in their promotion in the way of advertising. In fact, many companies often make mistakes in using grammar in writing advertising slogans to market their products. This study aims to identify the types of grammatical errors and focus on the types of errors used in advertising slogans by companies. This research method is descriptive qualitative. The method of writing advertising slogans uses a description of words or sentences that do not have a percentage or value in the form of numbers, where the researcher analyzes according to the type of data error category. From the results of the study, researchers found fifteen (15) advertising slogans were collected from companies via the internet.